2017
DOI: 10.1128/jvi.00168-17
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Gamma Prevents Infectious Entry of Human Papillomavirus 16 via an L2-Dependent Mechanism

Abstract: In this study, we report that gamma interferon (IFN-␥) treatment, but not IFN-␣, -␤, or -treatment, dramatically decreased infection of human papillomavirus 16 (HPV16) pseudovirus (PsV). In a survey of 20 additional HPV and animal papillomavirus types, we found that many, but not all, PsV types were also inhibited by IFN-␥. Microscopic and biochemical analyses of HPV16 PsV determined that the antiviral effect was exerted at the level of endosomal processing of the incoming capsid and depended on the JAK2/STAT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 84 publications
(136 reference statements)
0
21
0
Order By: Relevance
“…Although it appears that PV types across genera utilize similar intracellular pathways (26,27), different host proteins may be involved in this trafficking (28). We chose to examine PsV from two other oncogenic types for mitotic chromosome association.…”
Section: Fig 2 L1mentioning
confidence: 99%
“…Although it appears that PV types across genera utilize similar intracellular pathways (26,27), different host proteins may be involved in this trafficking (28). We chose to examine PsV from two other oncogenic types for mitotic chromosome association.…”
Section: Fig 2 L1mentioning
confidence: 99%
“…Thus, the raft culture system reflects an important aspect of constitutive innate immune activity of the epithelia in vivo. It is likely that the constitutive activation of IFNs in epithelial keratinocytes represents a barrier for the establishment and maintenance of HPV infections (21,91). Importantly, both of these markers of chronic IFN signaling were reduced by HPV16 in our experiments.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, the E5 peptide construct had 2 positive charge residues and the E7 peptide construct consisted of 2 positive and 11 negative charge residues. On the other hand, IFN-c has a key role in intracellular immunity against HPV infection (Day et al 2017). Our data showed that SPATAFTVYVFCFLLA (E5-type 18) and TLQEIVLHLEPQNELDPVDLL (E7-type 45) had the highest scores for stimulation of IFN-gamma against HPVs.…”
Section: Discussionmentioning
confidence: 71%